2014
DOI: 10.1007/s00590-014-1565-2
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar versus unipolar hemiarthroplasty for displaced femoral neck fractures in the elder patient: a systematic review and meta-analysis of randomized trials

Abstract: Both bipolar and unipolar hemiarthroplasty for the treatment of elderly patient suffering displaced femoral neck fracture achieve similar and satisfy clinical outcome in short-term follow-up. Unipolar hemiarthroplasty seems to be a more cost-effectiveness option for elderly patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 21 publications
0
29
0
1
Order By: Relevance
“…Thus, the reoperation incidence in the bipolar HA group is expected to be at least the equivalent to unipolar HA. Two meta-analyses comparing unipolar and biopolar HA support this conjecture 57,58 . But in our analysis, unipolar cemented HA exhibited lower reoperation incidence than other managements, and notably lower than did bipolar HA.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, the reoperation incidence in the bipolar HA group is expected to be at least the equivalent to unipolar HA. Two meta-analyses comparing unipolar and biopolar HA support this conjecture 57,58 . But in our analysis, unipolar cemented HA exhibited lower reoperation incidence than other managements, and notably lower than did bipolar HA.…”
Section: Discussionmentioning
confidence: 86%
“…Meta-analyses of randomized control trials were recently made available. Jia et al 20 confirmed a similar or better outcome in hip function, hip pain and quality of life in patients with bipolar implants, while Yang et al 19 reported a significantly lower acetabular erosion rate in the bipolar group (1.2%) compared to the unipolar group (5.5%). Liu et al, 18 however, did not report a statistically significant difference between the two implants.…”
Section: Discussionmentioning
confidence: 88%
“…However, some studies have not demonstrated superior functional outcome of bipolar hemiarthroplasty compared with their unipolar counterparts. 12,[16][17][18][19][20][21][22] There are also downsides of the bipolar system. The cost of the bipolar prosthesis is generally higher than unipolar implants.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main categories of hemi-arthroplasty prosthesis, when assessing head component utilised: unipolar hemi-arthroplasty (UH) (Figure 1A ) and bipolar arthroplasty (BH) (Figure 1B )[ 25 , 29 - 31 ]. An UH comprise a large single endo-prosthetic head component, while BH has both an endo-prosthetic “bipolar” head component and an inner metal bearing[ 25 , 29 - 31 ]. The theoretical benefit of the BH design, with its mobile bearing concept, is to reduce component-induced wear on the acetabulum[ 25 , 29 - 31 ].…”
Section: Prosthesis Head Component - Unipolar Vs Bmentioning
confidence: 99%
“…Despite the perceived simplicity of the hip hemi-arthroplasty procedure, there are a number of variations to the procedure[ 15 , 24 - 26 ]. These include the approach[ 26 - 28 ], the type of prosthesis head[ 25 , 29 - 31 ], the method of stem insertion[ 25 , 32 - 34 ], and the type of prosthesis assembly[ 35 ]. The optimal selection for each of these factors remains to be determined[ 15 , 24 - 26 ].…”
Section: Introductionmentioning
confidence: 99%